Pengaruh Debt To Equity Ratio (DER), Total Asset Turnover (TATO), Dan Struktur Aset Terhadap Return On Assets (ROA) Pada Perusahaan Property Dan Real Estate Yang Terdaftar Di Bursa Efek Indonesia Tahun 2016-2020 - Alif Firmansyah; Putri Amelia; Kinanti Rezi Budy Pramesti; Zulvi Azzahra Putri (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2022)
Research in this journal is to identify and analyze the effect of the Debt To Equity Ratio, Total Asset Turnover and Asset Structure on Return On Assets in Property and Real Estate Companies listed on the Indonesia Stock Exchange for the 2016-2020 period. The type of data used is secondary data in the form of the company's annual financial report. In this study there were 15 Property and Real Estate companies on the Indonesia Stock Exchange which were the research samples. The research method used is descriptive and quantitative research. The test was carried out with panel data regression using Eviews 10 with the panel data regression method using the Fixed Effect Model. The results showed that the Debt To Equity Ratio and Asset Structure had no effect on Return On Assets and Total Assets Turnover had a positive effect on Return On Assets. Debt To Equity Ratio, Total Assets Turnover and Asset Structure simultaneously influence Return On Assets.